Circulating Pregenomic Hepatitis B Virus RNA Is Primarily Full-length in Chronic Hepatitis B Patients Undergoing Nucleos(t)ide Analogue Therapy. (20th July 2020) - Anderson, Mark; Gersch, Jeffery; Luk, Ka-Cheung; Dawson, George; Carey, Ivana; Agarwal, Kosh; Shah, Pir; Dusheiko, Geoffrey; Lau, Daryl; Cloherty, Gavin
Abstract: Hepatitis B virus RNA is detectable in the serum of infected patients; however, the RNA species has been questioned. We tested 1827 specimens using a quantitative dual-target quantitative polymerase chain reaction assay and determined that full-length pregenomic RNA is the primary source. These results clarify the major identity of circulating HBV RNA species.